STUDI KESULITAN PENERJEMAHAN BAHASA INGGRIS-INDONESIA MAHASISWA JURUSAN PLS FKIP UNIVERSITAS BANDUNG RAYA - Annie Susany (Universitas Insan Cendekia Mandiri, 2019)
This is a report of a study designed to examine the PLS students’ difficulties in translating English texts into Indonesian. This is also to explore the solution given by lecturers to overcome their difficulties in translating English texts into Indonesian. Using descriptive analytical method, this study aimed to observe the difficulties and its solutions in translating a text. Data concerning the students’ difficulties were collected by using documentation analysis in the form of translated version texts (work of English-Indonesian translation of students). Meanwhile, data regarding the solutions given by four PLS Students and 10 students in translating English texts were collected by administering interview. The data were then analyzed and interpreted analytically. The results showed that the students found it difficult to translate English texts into Indonesian, particularly in terms of vocabulary size and phrases. The most difficult phrases to be translated are prepositional phrase, verb phrase, participle phrase, noun phrase and infinitive phrase. However, to solve their difficulties in translating English texts into Indonesian, students were in the same ideas that the students should improve their language competency, such as structure, syntax, and vocabulary. In relation to solve the difficulty in translating phrases, the students should focus more on learning such language components. In addition, the students had also the same ideas that to solve their translation problem, they would focus more on practicing to translating the various English texts while learning language components.